Kinerja, motivasi, dan networking credit marketing officer sebagai faktor penentu volume penjualan PT Astra Credit Companies Makassar - Abdillah, Muhammad; Kadir, Muhammad Akob; Ma'ruf Idris, Muhummad; Baharuddin, Baharuddin (Journal of Management and Digital Business, 2024)
This study analyzes the influence of performance, motivation, and networking of Credit Marketing Officers (CMOs) on the sales volume of car financing at PT Astra Credit Companies (ACC) Makassar Branch. A quantitative study with a survey design was conducted on 45 active CMOs in 2023. Data collection was carried out using structured questionnaires, and data analysis was performed through multiple regression to determine the relationships between independent and dependent variables. The study aims to identify factors influencing sales volume in the context of automotive financing. The results show that performance, motivation, and networking have a significant simultaneous effect on sales volume. Motivation proved to have the largest contribution, where an increase of one unit in motivation could raise sales volume by 15%. Partially, the variables of motivation, performance, and networking positively impact sales volume. The study emphasizes the importance of optimizing CMO performance and motivation, as well as strategic network management, to enhance the Companies' competitiveness in the automotive financing industry.